Spirit Filantropi Islam dalam Aktivitas Sosial di Masa Pandemi Covid-19 - Muhammad Erfan; Ahmad Dakhoir; Mazrur Mazrur (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2021)
The government's policy to limit the movement of the community to suppress the spread of the Covid-19 virus affects the economic situation of most people, especially during a pandemic like this time. The community is expected to be able to contribute according to their respective conditions and abilities. One of the contributions that can be made is in the form of philanthropy. Philanthropy is not limited to loving others related to the economic field, such as zakat, infaq, almsgiving, waqf, or others, but has a broader meaning. This study aims to determine the spirit of Islamic philanthropy in the social activities of members of the Majelis Nurul 'Ilmi STMIK Palangkaraya during the Covid-19 pandemic. This research is qualitative research using observation and documentation data collection techniques. Data analysis in narrative or descriptive form using inductive thinking. The results of this study found that the social activities of the members of Majelis Nurul 'Ilmi were carried out based on the spirit of Islamic philanthropy.